Policy borrowing for a world-class university: a case of a writing center in Japan. Issue 5 (20th October 2019) - Okuda, Tomoyo
ABSTRACT: Increased pressures of internationalization compel universities worldwide to search for successful education models and frameworks that can enhance their entrepreneurial status and international competitiveness. This study aims to explore the political interests, power dynamics, and consequences of transferring educational systems, models, and concepts across context, by focusing on the popularity of the writing center (a writing support service originating in the United States) in Japan. To examine the political and socio-economic factors that motivated a Japanese university to establish a writing center, I trace the process of the writing center's establishment from documents and interviews with five university staff involved in the planning. Policy borrowing as a conceptual framework is employed to illuminate the ways in which participants exercised their agency and justified the writing center in relation to the university's internationalization mission. Given the findings, I discuss the impulses, externalizing potentials, and reference societies that attracted administrators to the idea of the writing center and critically examine the policy borrowing practices that aim to internationalize higher education.